SISTEM INFORMASI GEOGRAFIS LOKASI PERGURUAN TINGGI DI DAERAH ISTIMEWA YOGYAKARTA BERBASIS MOBILE ANDROID - Victor Motumona; Uning Lestari; Erfanti Fatkhiyah (Jurusan Informatika INSTITUT SAINS & TEKNOLOGI AKPRIND YOGYAKARTA, 2016)
The information system is an information technology that is currently growing very rapidly. The information can be accessed easily using a smartphone to quickly, safely and effectively is obviously very helpful for anyone who uses it. Including one of a Geographic Information System ( GIS ), which became one of the media information retrieval, especially for information related to the data search program in Yogyakarta existing colleges One of the popular GIS technology is the Google Maps API. With this technology could be a location for special purposes such as making college location. This technology will be implemented in the system so that it can help students or the general public in finding infrormasi in the city of Yogyakarta Special Region which is presented in the form of android applications. Yield data study programs and colleges intangible an application program based on Android, which is expected to help facilitate user or prospective students who want to search for a course or college in the area of Yogyakarta, which can easily obtain information, the location of the distance as well as navigate to peguruan high in Yogyakarta.